Frequency and risk factors for injury of the inferior alveolar nerve during surgical extraction of the impacted lower third molars - Dubovina, Dejan; Matijevic, Stevo; Djordjevic, Filip; Stanisic, Jelena; Mihailovic, Branko; Lazic, Zoran (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. The injury of inferior alveolar nerve during a surgical extraction of impacted lower third molars, followed by sensory disturbance, is, for the patient, an extremely unpleasant complication. The aim of this study was to determine the frequency of this complication after the third molar surgery and its frequency depending on a tooth position and tooth relation to the mandibular canal. Methods. In this study, 800 surgical extractions of the impacted lower third molar were performed. The position of the impacted tooth was recorded according to the Winter classification, as well as the ratio of their root tips to the mandibular canal using the Tanaka et al. and Rood and Shebab classifications. Results. The frequency of the recorded post extraction sensory disturbance was 2.25%, most frequently when teeth were in the mesioangular position. Concerning Tanaka and al. classification, the incidence of injuries was inversely proportional to the increase of distance between roots and mandibular canal with the statistical significance in cases where mandibular canal overlaps more than a half of the root of the tooth (p = 0.001). Considering the radiological signs recommended by Rood and Shehab, a higher frequency of the inferior alveolar nerve injury was recorded when illumination in the area of the root tips was present and when the loss of linear overshadowing characterized by the “roof” and the “bottom” of the mandibular canal were observed, or diversion of the canal and root deflection, but without a statistical significance. Conclusion. The superposition of the mandibular canal with the lower third molar roots at the panoramic radiographies may increase a possibility of the inferior alveolar nerve injury. The angulations of the impacted lower third molar as well as the vicinity of the tips of its roots to the content of the mandibular canal, do not significantly affect the frequency of the nerve injury
Keywords: molar, third; tooth, impacted; tooth extraction; mandibular nerve; oral surgical procedures; paresthesia